2006
DOI: 10.1080/13698570600677266
|View full text |Cite
|
Sign up to set email alerts
|

Risk management after stroke: The limits of a patient-centred approach

Abstract: Current strategies to reduce risk of stroke recurrence are reported to be inadequate. This paper reports findings from a qualitative observational study investigating how risk management is practiced in the stroke outpatient clinic. The 'patient-centred' approach has been proposed as a mechanism to improve the quality of health care delivery. It is thought that focusing on patients' wants, needs and preferences is ethically desirable and will lead to improved health outcomes. However risk management strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…These understandings were largely derived from contact with a primary health care system where national guidance on threshold levels has become the marker of patient adherence. These responses may also be reflective of the process identified by Redfern et al (2006) in their study of stroke patients, which concluded that doctors primarily focused on biological rather than social or psychological aspects of stroke risk management. This was seen to reflect not only doctors primary concern with clinical factors, but a limited ability to address psychological or social concerns of patients (Redfern et al 2006: 138).…”
Section: Discussionmentioning
confidence: 90%
“…These understandings were largely derived from contact with a primary health care system where national guidance on threshold levels has become the marker of patient adherence. These responses may also be reflective of the process identified by Redfern et al (2006) in their study of stroke patients, which concluded that doctors primarily focused on biological rather than social or psychological aspects of stroke risk management. This was seen to reflect not only doctors primary concern with clinical factors, but a limited ability to address psychological or social concerns of patients (Redfern et al 2006: 138).…”
Section: Discussionmentioning
confidence: 90%
“…This interpretation is supported by the finding of a three‐way interaction between doctor's behaviours, patient role, and time of measurement for personal self‐esteem, with traditional patients reporting an increase in self‐esteem and consumerist patients no change in self‐esteem when treated with disrespect. Traditional patients appear to have chosen to focus on intragroup comparisons deriving positive self‐esteem from seeing themselves as good and compliant patients (Redfern et al., 2006), while consumerist patients might have chosen to attribute the maltreatment to being a consumerist patient to defend their self‐worth (Smith & Mackie, 2000). When respected, consumerist patients might have left the patient role to interact at an interpersonal level with the doctor (Otten & Mummendey, 2000), which could explain the greater increase in personal self‐esteem compared to the traditional patient.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that such patients value deference towards the doctor (Hibbard et al., 2005), trust the doctor's competence (Arora, Ayanian, & Guadagnoli, 2005; Lupton, 1997), believe an obedient role is appropriate (Gaard, 2006), prefer that the doctor makes the medical decisions (Beisecker, 1990), are worried about offending the doctor by making their own treatment decisions (Arora et al., 2005), and have little confidence in their ability to influence the medical encounter (Arora et al., 2005). Such patients are often regarded as “good patients” by medical staff (Redfern, McKevitt, & Wolfe, 2006), in part because they cause the least trouble (Lorber, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Based on existing evidence and our theoretical work, we had hypothesized that a multiple component approach targeting patient, caregiver, and GP, 3 over time points, would have a stronger influence on risk factor management than a single component intervention. However, the approach we adopted may still have been insufficient to address some of the barriers to secondary prevention management identified in our early work; targeting individual stroke survivors and caregivers with evidence-based advice on optimal risk factor management may be insufficient to influence routine access to health services or to encourage those with suboptimal risk factor management to challenge GPs about inappropriate decisions 27 ; targeting GPs may be insufficient to ensure that those with suboptimal risk factor management are recalled for further investigation and may be less effective than payment in influencing GP prescribing practices. 26,27 In the trial we defined our choice of outcome measures to reflect guidelines for best practice in poststroke risk factor management current at the time the protocol was written and these were based on receipt of treatment.…”
Section: Wolfe Et Al Stop Stroke Secondary Prevention Trial 2473mentioning
confidence: 99%